The southern Central America puzzle: Cronology and structure. A review - Tournon, Jean (2007)
From northern Costa Rica to eastern Panama oceanic rocks are extensively exposed along the Pacific margin of Isthmic Central America. For the past 30 years, their nature and significance were subject to debate. This study distinguishes numerous units using the following criterions: ages of igneous and sedimentary rocks, petrological and geochemichal features, structural setting and ages of the sedimentary "covers". New field, radiometric and stratigraphical data are compared with available data published in recent papers. Strong disparities are noticed for ages, from Lias-lower Dogger to Eocene and petrological patterns: mantle peridotites, several tholeiitic and alkaline series. Various units are mélange formations made of exotic blocks unknown elsewhere. We propose that these disparate units were emplaced by two contrasting processes: 1) Closing of a Mesozoic northern oceanic basin by northward convergence and emplacement of an E-W 150 km ophiolitic suture; 2) successive accretions of terranes originated in the Pacific plate and corresponding to possible oceanic plateau basalts and seamounts.